2017
DOI: 10.1111/coep.12252
|View full text |Cite
|
Sign up to set email alerts
|

Small Business Borrowing and Peer‐to‐peer Lending: Evidence From Lending Club

Abstract: We investigate the ability of small business borrowers to signal to investors their credit worthiness through the use of text descriptions in the peer‐to‐peer lending market. Specifically, we examine the relationship between the loan description written by a borrower and whether or not the project is funded by investors. Using textual analysis, we find that small business loan descriptions can be used to predict the likelihood that the loan will be funded. We also find that an index, created from a textual ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 68 publications
1
21
0
2
Order By: Relevance
“…A vast amount of literature has documented that the lack of ability to access necessary external finance is one of the crucial unfavorable factors that negatively affect innovation and sustainable growth of small businesses [17,38,46,47]. For instance, Nowak et al [17] found that, to mitigate financing difficulty, small business loan descriptions can be used as a tool to signal borrowers' worthiness, which can predict the likelihood that the loan will be funded, and investors can make investment decisions based on proper and relevant signals given by the small business borrowers through the loan description. Cosh et al [47] considered what affects rejection rates for financing from different types of investors, including private individuals.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A vast amount of literature has documented that the lack of ability to access necessary external finance is one of the crucial unfavorable factors that negatively affect innovation and sustainable growth of small businesses [17,38,46,47]. For instance, Nowak et al [17] found that, to mitigate financing difficulty, small business loan descriptions can be used as a tool to signal borrowers' worthiness, which can predict the likelihood that the loan will be funded, and investors can make investment decisions based on proper and relevant signals given by the small business borrowers through the loan description. Cosh et al [47] considered what affects rejection rates for financing from different types of investors, including private individuals.…”
Section: Related Literaturementioning
confidence: 99%
“…Our paper, therefore, contributes to the growing literature on Internet finance as well as the broader literature on crowdfunding. Recent investigations include [10][11][12]14,15,[17][18][19][20][21][22][23][24][25][26][27]. Given that the explosive penetration of the Internet and Mobile Internet that has laid a sound foundation in China, which has been rapidly skyrocketing (China has greater Internet and mobile Internet development among emerging market economies with penetration ratios of 45% and 37.1%, respectively, in 2013, reported by Lei [19]), our study has important and timely implications not only for academics and practitioners, but for policy makers as well.…”
Section: Introductionmentioning
confidence: 99%
“…Asset information includes real estate, car property, and monthly wage income of borrowers, whereas personal physical signs include age, credit rating, educational background, and marital status of borrowers. As for soft information, the focus is on loan description, appearance, and social relations of borrowers, wherein loan description refers to loan information voluntarily written by borrowers, on the basis of which investors can make investment decisions (Nowak, Ross & Yencha, 2018). Many scholars discussed the content level of loan description, for example, vocabulary type used in loan description, which is manifested by character figures (Herzenstein, Sonenshei & Dholakia, 2011;Wang & He, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The variables used in this study were loan amount, loan period, interest rate, installment, income, debt-to-income ratio, and FICO score. The analytical method used was Tobit regression, and results indicated that loans with low FICO scores can still influence lender investment decisions through descriptions made in the marketplace (Nowak et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al (2017) and Nowak et al (2018) show that the higher the interest rates offered, the higher the likelihood that a loan will be granted. The hypothesis built on this variable is as follows:…”
Section: Interest Ratementioning
confidence: 99%